Analysing consonantal speech sounds: a sociophonetic approach - Chan, M (2011)
Spectrography has been employed for the analysis of speech sounds in the last decades, and many signi?cant discoveries about speech has been made using this technique. This poster will present techniques which are employed in spectrographic analysis of consonantal speech sounds in sociophonetic studies. The formant pro?les of various consonants as well as the question of how one particular ’consonant’ can be realised in di?erent ways will be explored. The aim is to uncover the acoustic properties of consonantal sounds which are signi?cant in explaining how speakers present their own identities and perceive those of others.